Kesantunan Berbahasa Dalam Bertanya Dan Menjawab Pertanyaan Dalam Webinar - Mas’ud Muhammadiyah; Thrisia Monica; Sarniyati Sarniyati; Moza Suzana; Lestari Budianto; Muh. Safar (Journal on Education, 2023)
This study aims to explain language politeness in asking and answering questions on webinars. This qualitative research has various research data analyzed by transcribing, inventorying, identifying, classifying, formulating and explaining, as well as concluding and verifying data. Research findings: (1) speech acts of asking and answering questions in the Webinar; (2) the methods used by speakers in the Webinar to form polite speech acts of asking and answering questions. There are two types of speech acts of asking and answering questions, total and partial speech acts. Language politeness strategies focused on asking and answering questions in the Webinar are determined by analyzing speech based on maxims. By complying with the 6 politeness maxims accompanied or not accompanied by prioritizing maxims, the speech act of asking and answering questions is classified as polite.